Cimetidine-induced androgenic failure causes cell death and changes in actin, EGF and V-ATPase immunoexpression in rat submandibular glands - Manzato, Mariane Castro [UNESP]; de Santi, Fabiane; da Silva, André Acácio Souza [UNESP]; Beltrame, Flávia L.; Cerri, Paulo S. [UNESP]; Sasso-Cerri, Estela [UNESP] (Wiley, 2021)
Submandibular gland (SMG) is responsive to androgens via androgen receptor (AR). We verified whether cimetidine induces androgenic dysfunction in SMG, and evaluated the structural integrity, cell death and immunoexpression of actin, EGF and V-ATPase in androgen-deficient SMG. Male rats received cimetidine (CMTG) and control animals (CG) received saline. Granular convoluted tubules (GCTs) diameter and number of acinar cell nuclei were evaluated. TUNEL and immunofluorescence reactions for detection of AR, testosterone, actin, EGF and V-ATPase were quantitatively analysed. In CG, testosterone immunolabelling was detected in acinar and ductal cells cytoplasm. AR-immunolabelled nuclei were observed in acinar cells whereas ductal cells showed AR-immunostained cytoplasm, indicating a non-genomic AR action. In CMTG, the weak testosterone and AR immunoexpression confirmed cimetidine-induced androgenic failure. A high cell death index was correlated with decreased number of acinar cells, GCTs diameter and EGF immunoexpression under androgenic dysfunction. Actin immunofluorescence decreased in the SMG cells, but an increased and diffuse cytoplasmic V-ATPase immunolabelling was observed in striated ducts, suggesting a disruption in the actin-dependent V-ATPase recycling due to androgenic failure. Our findings reinforce the androgenic role in the maintenance of SMG histophysiology, and point to a potential clinical use of cimetidine against androgen-dependent glandular tumour cells.
Keywords: antiandrogen; apoptosis; AR; salivary glands; testosterone